WHAT IS SUCCESSFUL AGING? COMPARING FRAMEWORKS FOR SUCCESSFUL AGING WITH CULTURAL PERSPECTIVES - Jensen, A. (Innov Aging, 2017)
“Successful aging” has different meanings in different cultures. Our purpose was to examine whether published frameworks for successful aging would align with the values and perspectives of older adults across cultures. We identified studies on elderly populations published from 1997 to 2016 that addressed older adult perspectives on successful aging, or that applied the 1997 Rowe and Kahn framework for successful aging to older adult cohorts. Additionally, we compared findings from these studies with framework found in the 2015 WHO World Report On Ageing and Health. We identified studies from a variety of cultures, including peoples from China, Japan, the Netherlands, the United States, and Nigeria. Key concepts identified from lay perspectives were much broader in scope than the three key criteria in the Rowe and Kahn framework: absence of disease, high physical and cognitive functioning, and engagement. Further concepts we identified included coping, financial security, spirituality, well-being, longevity, and life satisfaction. While published frameworks and cultural values overlapped, key concepts varied in importance from culture to culture. Based on our findings, we propose a framework that includes a comprehensive set of key concepts drawn from multiple cultures, and that allows healthcare workers and policy makers to weigh these concepts differently according to needs and views of each society. For example, Alaska Natives more highly valued well-being and spirituality, whereas Japanese-American men more highly valued financial security. A flexible framework that allows key concepts to be weighted differently depending on culture may be beneficial for defining and understanding successful aging.